Analysis of genetic polymorphisms and drug resistance mutations in the NS5 region of HCV genome (Flasuviricetes: Amarillovirales: Flaviviridae: Hepacivirus C) in samples obtained in 2022–2023 from HIV-infected treatment-naive residents of Altai Krai - Ilya A. Lapovok; Arina V. Syrkina; Alina A. Kirichenko; Anastasia V. Shlykova; Natalya V. Lukyanenko; Tatyana V. Safyanova; Arina E. Safronova; Valery V. Shevchenko; Dmitry E. Kireev (Вопросы вирусологии)
Introduction. Altai Krai is a region with an unfavorable situation of HIV-1 and HCV infection, as well as HIV-1 and HCV coinfection. Due to this, it is necessary to study the HCV genetic variants and their drug resistance (DR) to direct-acting antivirals (DAAs) in patients with HIV-1 and HCV coinfection.